2006
DOI: 10.1007/s10641-006-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine Typology and the Structuring of Fish Communities in South Africa

Abstract: Some 190 South African estuaries, covering all biogeographic provinces within the region, were classified into three types based on a combination of mouth condition and estuary size (surface area). The fish communities of the estuary types within each zoogeographic region were described and compared. Multivariate analyses revealed that each estuary type contained somewhat distinct fish communities. In addition, the study identified common patterns in species richness and ichthyofaunal composition. Open estuari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 27 publications
7
53
0
2
Order By: Relevance
“…Nevertheless, as demonstrated in this study and supported by others (e.g. Edgar et al 1999;Harrison and Whitfield 2006a), estuarine type and, in particular bar-state, is a major driver in structuring spatial differences in estuarine fish communities in temperate, microtidal waters. estuaries in this study have characteristics that probably reflect evolutionary adaptations to being disconnected from the sea and its moderating influences (e.g.…”
Section: Importance Of Spatial Scale In Explaining Differences Among supporting
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, as demonstrated in this study and supported by others (e.g. Edgar et al 1999;Harrison and Whitfield 2006a), estuarine type and, in particular bar-state, is a major driver in structuring spatial differences in estuarine fish communities in temperate, microtidal waters. estuaries in this study have characteristics that probably reflect evolutionary adaptations to being disconnected from the sea and its moderating influences (e.g.…”
Section: Importance Of Spatial Scale In Explaining Differences Among supporting
confidence: 86%
“…Whitfield 1999;Harrison and Whitfield 2006a). Indeed, while not the main focus of their study, Harrison and Whitfield (2008) demonstrated the latter to be true for fish guild compositions in three estuary types and bioregions across South Africa.…”
Section: Importance Of Spatial Scale In Explaining Differences Among mentioning
confidence: 95%
See 1 more Smart Citation
“…At this large scale, estuarine fish communities are related to environmental conditions (river flow and temperature) but also to biogeographic species distribution. Main features of estuaries thus strongly influence fish habitats and communities at different scales (Roy et al, 2001;Saintilan, 2004;Harrison and Whitfield, 2006). Consequently, taking into account the large-scale driving factors (Keddy, 1992), macroscopic studies of the relationships between environment and fish assemblage structure may help, first, to understand the functioning of estuarine ecosystems, and then, to assess their ecological status so that appropriate management decisions can be taken (Brown, 1995;Peterson, 2003;Engle et al, 2007).…”
mentioning
confidence: 99%
“…Power et al, 2000;Daufresne et al, 2003) or from spatial comparisons of a number of different sites (e.g. Ley, 2005;Harrison and Whitfield, 2006). Previous very large scale American, South African and Australian studies have found estuary mouth configuration (Monaco et al, 1992;Edgar et al, 2000;Ley, 2005;Harrison and Whitfield, 2006), estuarine water area (Monaco et al, 1992;Pease, 1999;Harrison and Whitfield, 2006), latitude (Edgar et al, 1999;Pease, 1999;Harrison and Whitfield, 2006) and catchment area hydrology (Ley, 2005) to be the main abiotic determinants of species richness.…”
mentioning
confidence: 99%